In vitro and in vivo studies of the endocrine disrupting potency of cadmium in roach (Rutilus rutilus) liver. Issue 2 (30th June 2015) - Gerbron, M.; Geraudie, P.; Xuereb, B.; Marie, S.; Minier, C.
Highlights: Ex vivo and in vivo experiments suggest estrogen receptor-driven effects of cadmium. CdCl2 is strongly anti-estrogenic when co-exposed to E2. CdCl2 + E2 significantly inhibit vtg and erα mRNA expressions. CdCl2 compromises the E2-mediated induction of the ar mRNA expression in vivo . Abstract: Cadmium has been reported to exert estrogenic, antiestrogenic or both effects in vertebrate species. To elucidate the endocrine disrupting action of CdCl2, ex vivo and in vivo experiments were performed in roach ( Rutilus rutilus ). Roach liver explants were exposed to a range of CdCl2 concentrations alone (0.1–50 μM) or with an effective concentration (100 nM) of 17β-estradiol (E2). In addition, juvenile roach were intraperitoneally injected with CdCl2 (0.1–2.5 mg/kg) with or without 1 mg E2/kg. Subsequent analysis evaluated the effect of CdCl2 on vitellogenin (VTG) synthesis both at the mRNA and protein level, on estrogen receptors (erα and erβ1) and on androgen receptor (ar) mRNA expression. Ex vivo and in vivo experiments indicated that CdCl2 is strongly anti-estrogenic as, when co-exposed to E2, CdCl2 significantly inhibited VTG production as well as vtg and erα mRNA expressions. Moreover, CdCl2 compromised the E2-mediated induction of the ar mRNA expression in vivo .